Efficacy and safety of topical minocycline preparations for papulopustular rosacea: a systematic review and meta-analysis - Alamri, Awadh; Alsamadani, Abdulrahman H.; Alraddadi, Rose A.; Kalantan, Mulham; Khafaji, Randa; Bashrahil, Bader; Bogari, Hassan; Kadasa, Athoub; Jfri, Abdulhadi (Frontiers in Medicine, 2025)
BackgroundRosacea is a chronic inflammatory skin condition. Papulopustular rosacea (PPR), one of the subtypes of rosacea, presents with papules and pustules (Pelle, 2008). Topical minocycline allow the delivery of high concentrations of the medication to the skin while decreasing systemic exposure thereby evading side effects (Jones et al., 2021, Webster et al., 2020). This study aims to review the literature to delineate the efficacy and safety of topical preparations of minocycline in the treatment of moderate to severe papulopustular rosacea.MethodsThis systematic review included randomized clinical trials (RCT) only that compared the efficacy and safety of 1.5% minocycline foam and 1%, 3% minocycline gel versus placebo in patients with moderate to severe papulopustular rosacea. We performed a systematic search in Medline, Cochrane Central Register of Controlled Trials (CENTRAL), Scopus, and ClinicalTrials.gov. Efficacy outcomes included the absolute change in inflammatory lesion counts, the percentage change in the inflammatory lesion count, the percentage of participants achieving Investigator Global Assessment (IGA) with improvement of at least two grades, and the proportion of individuals that achieved an IGA 0/1 score (“clear” or “almost clear”). This paper was conducted in adherence to PRISMA guidelines. Also, we have registered our protocol in PROSPERO (CRD42023447486). Quality assessment of the included studies was conducted using ROB-2 tool. Additionally, we have assessed the level of evidence using GRADE too. The analysis was performed using RevMan.ResultsFive randomized controlled trials with low risk of bias were included in the quantitative synthesis with a total of 2,453 enrolled participants. Minocycline (FMX103) 1.5% foam yielded statistically significant results in terms of IGA score indicating treatment success [Risk Ratio (RR) = 1.31, 95% confidence interval (CI) = 1.04–1.66, P = 0.02]. FMX103 and minocycline gel 1% and 3% had significant results in absolute change in inflammatory lesion count (RR = 3.49, 95% CI = 2.61–4.36, P < 0.00001). Change in inflammatory lesion count from baseline with minocycline 1.5% foam was significantly reduced (RR = 9.45, 95% CI = 5.84–13.06, P < 0.00001). Other indicators of symptom reduction were not significant for both foam and gel preparations.ConclusionOur findings suggest that topical preparations of minocycline provide statistically significant results in reducing absolute inflammatory lesion count and having IGA treatment success among patients with moderate to severe papulopustular rosacea. Further studies, however, should assess the efficacy of different concentrations and combinations of minocycline to better delineate the effect of this drug in the clinical aspect.Systematic review registrationPROSPERO, identifier CRD42023447486, https://www.crd.york.ac.uk/PROSPERO/view/CRD42023447486.